Pengembangan Video Animasi MAPS sebagai Edukasi Manajemen ASI Perah untuk Meningkatkan Cakupan ASI Eksklusif - Dede Gantini; Maahira Kamila Khairunnisa Sutisna; Sariestya Rismawati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
The global exclusive breastfeeding rate currently stands at 48%, slightly below the 50% global goal for 2025. In Indonesia, although the coverage rate has improved to 74.73%, it remains considerably below the national target of 80%, as stipulated by national policy and Minister of Health Decree No. 450/Menkes/IV/2004. This study aimed to evaluate the feasibility of an educational medium: an animated video called MAPS (Manajemen ASI Perah Sehat), designed to enhance mothers' knowledge about expressed breast milk and support exclusive breastfeeding practices. The research employed a Research and Development (R&D) approach through six stages. The subjects were 10 breastfeeding mothers with infants aged 0–3 months, selected via purposive sampling. Evaluation instruments included expert assessment questionnaires and user trials.The validation results confirmed the medium's high feasibility: Media 93% and Material 97.2%. User testing yielded a score of 90.38%, while the small-scale product trial resulted in an excellent score of 98.3%. The conclusion is that the MAPS animated video is highly feasible to be used as an educational tool. It effectively enhances mothers' understanding of expressed breast milk management, thereby supporting the success of exclusive breastfeeding, especially for working mothers.